Glass fiber reinforced welding method, welded structural part and application of welded structural part
By spraying glass fiber reinforced welding rib materials and laser welding, the problems of cumbersome processing of welding ribs, material limitations and unevenness after welding in the prior art are solved, and an efficient and automated welding process is achieved, and welding performance and sealing are improved.
Patent Information
- Application Number
- CN202510023563.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
The existing laser transmission welding process has cumbersome machining process in the processing of weld ribs in the weld area. The workpiece material needs to add light absorbent to meet the absorbance of the weld ribs. There is also unevenness on the surface of the workpiece after welding, which limits the application of laser welding technology in the field of flow batteries.
The spraying device is used to spray the glass fiber-reinforced welding rib material onto the surface of the workpiece to form an integral welding rib structure, and the upper and lower workpieces are welded into one through laser welding, solving the problems of cumbersome processing of welding ribs and workpieces and improving the flatness of the workpiece after welding.
The automatic spraying process of welding ribs and workpieces is realized, the laser transmission welding process is simplified, the bonding and sealing performance of welding is improved, the unevenness of the workpiece surface after welding is avoided, and the light absorption and heat conduction ability of the welding rib structure are enhanced.
Smart Images

Figure CN119794563A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealed welding assembly molding, and in particular to a welding method and a welding structure part reinforced with glass fiber and applications thereof. Background Art
[0002] As a high-precision and high-efficiency material connection method, laser welding technology has been widely used in the field of industrial manufacturing. It uses a high-energy-density laser beam as a heat source to locally heat the material to be welded to a molten state, thereby forming a strong welded joint. Compared with traditional arc welding, resistance welding and other methods, laser welding has the advantages of small heat-affected zone, low welding deformation, high welding speed and high degree of automation.
[0003] In recent years, with the rapid development of the new energy field, especially the advancement of flow battery technology, the requirements for the sealing of battery components have become increasingly higher. Flow battery is an energy storage system based on liquid electrolyte, and its working principle relies on the redox reaction of positive and negative active substances in the electrolyte. In order to ensure the normal operation of the battery, it is necessary to ensure that the electrolyte does not leak, which requires the structural design of the battery, especially the welding and sealing performance between the plate and frame to meet high standards.
[0004] At present, the plate-frame welding of flow batteries mainly adopts traditional welding technology, such as resistance spot welding or ultrasonic welding, etc. However, these technologies are often difficult to meet the actual needs when facing the plate-frame with complex geometric shapes and strict requirements on sealing. In addition, traditional welding technology also has problems such as insufficient welding strength and easy generation of micro cracks after welding, which will affect the service life and safety of flow batteries.
[0005] In this context, the development of a new welding technology has become an inevitable trend. Laser transmission welding technology has become an ideal choice for flow battery plate frame welding due to its unique non-contact processing characteristics and the ability to achieve precision control. In addition, in order to further improve the corrosion resistance and mechanical strength of the welding parts, the technology of spraying the weld after laser welding has also been introduced into the manufacturing process of flow batteries.
[0006] The traditional laser transmission welding process has certain limitations, especially in the processing of weld ribs in the weld area. For example, the integrated machining process of the weld rib and the workpiece (lower workpiece) is cumbersome; in order to meet the light absorption of the weld rib, the material of the workpiece (lower workpiece) is restricted; when the workpiece size is large, the processing accuracy is low, and there is a certain degree of unevenness on the workpiece surface after welding, which limits the application of laser welding technology in the field of liquid flow batteries. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a welding method and a welded structure using glass fiber reinforcement and its application. The present invention can solve the problem of cumbersome machining process of welding rib and workpiece integration, solve the problem of adding additional light absorbent to the workpiece to meet the light absorption of the welding rib, and overcome the problem of uneven surface of the workpiece after welding.
[0008] In order to achieve the above object, the present invention provides a first aspect of a welding method using glass fiber reinforcement, which comprises the following steps:
[0009] Step S1: using a spraying device to spray a first welding rib material into the groove of the lower workpiece, and after cooling and solidification, forming a preliminary welding rib structure; the first welding rib material includes a first thermoplastic material, an adhesive and a light absorbent;
[0010] Step S2: using a spraying device to spray a second welding rib material onto the surface of the preliminary welding rib structure, and wrapping the preliminary welding rib structure with the second welding rib material, and after cooling and solidification, forming an integral welding rib structure, and obtaining a lower workpiece having a welding rib structure; the second welding rib material includes glass fiber;
[0011] Step S3: superimpose and fix the upper workpiece and the lower workpiece with the weld rib structure, use a laser welding device to emit a laser beam, pass through the upper workpiece, act on the overall weld rib structure, melt the overall weld rib structure, and at the same time apply a downward clamping force to weld the upper workpiece and the lower workpiece into one, so as to obtain a welded structural part.
[0012] According to a specific embodiment of the present invention, preferably, the thickness of the lower workpiece is greater than 3 mm. It should be noted that the thickness here refers to the maximum thickness of the non-groove portion of the lower workpiece. By controlling the thickness of the lower workpiece to be greater than 3 mm, the thickness of the lower workpiece will not be too thin to avoid being melted through by the molten weld rib structure.
[0013] According to a specific embodiment of the present invention, preferably, the depth of the groove of the lower workpiece is 0.3-0.5mm, the width is 1-5mm, and the groove of the lower workpiece has a plurality of raised stripes with a width of 0.1±0.03mm and a height of 0.2±0.05mm. By providing a plurality of raised stripes, the bonding and fixing of the first welding rib material in the groove is facilitated. In addition, the present invention does not impose any special restrictions on the length of the groove of the lower workpiece, which can be determined based on the length of the lower workpiece.
[0014] According to a specific embodiment of the present invention, preferably, the light transmittance of the upper workpiece is above 30%. The light transmittance is tested and obtained according to the record in GB / T 2410-2008.
[0015] According to a specific embodiment of the present invention, preferably, the method further comprises, before step S1, sequentially performing plasma treatment, supercritical carbon dioxide cleaning, nano-spraying and infrared drying on the upper workpiece and the lower workpiece. These pre-treatment steps can be performed according to methods in the prior art, and the present invention does not impose any special restrictions on them.
[0016] According to a specific embodiment of the present invention, preferably, in step S1, the melting point of the first thermoplastic material is 170-185° C. More preferably, the first thermoplastic material is the same as the main body material of the lower workpiece. Further preferably, the first thermoplastic material includes polypropylene (PP), acrylonitrile-butadiene-styrene copolymer (ABS) or polyphenylene oxide (PPO), and further preferably polypropylene (PP).
[0017] According to a specific embodiment of the present invention, preferably, in step S1, based on the total mass of the adhesive as 100%, it includes: 50%-70% of a second thermoplastic material, 10%-20% of carbon fiber, 1%-5% of graphene, 0.2%-0.8% of a first coupling agent, 0.1%-0.4% of a first antioxidant, 0.05%-0.2% of an antibacterial agent, 5%-10% of hollow glass microspheres, 3%-7% of nanoclay, and a first solvent remainder. More preferably, the main material of the second thermoplastic material is the same as the first thermoplastic material; further preferably, the second thermoplastic material includes modified polypropylene (mPP). More preferably, the average length of the carbon fiber is 0.05-1mm and the average diameter is 1-10μm. More preferably, the graphene includes graphene nanosheets, the average thickness of which is 1-20nm and the average diameter of the sheet is 10-50μm. More preferably, the first coupling agent includes a silane coupling agent, such as an aminosilane coupling agent. More preferably, the first antioxidant includes a hindered phenol antioxidant, such as Irganox 1010. More preferably, the antibacterial agent includes a silver ion antibacterial agent. More preferably, the hollow glass microspheres have an average particle size of 100-250 μm and a bulk density of 0.10-0.30 g / cm 3 More preferably, the nanoclay includes one or more of nano-montmorillonite, nano-kaolin and nano-halloysite, and the average particle size of the nanoclay is less than 100 nm. More preferably, the first solvent includes epoxy acrylate oligomer and the like.
[0018] The present invention uses the above composition as an adhesive, wherein the second thermoplastic material can improve the bonding force between the first thermoplastic material and the workpiece; carbon fiber and graphene can improve the bonding strength, while improving the light absorption capacity and thermal conductivity; the coupling agent can improve the bonding force between the first thermoplastic material, the adhesive and the light absorber; the hollow glass microspheres and nanoclay can further improve the bonding pull-out force; the first solvent can further enhance the bonding property. Through the synergistic effect between the various components of the adhesive of the present invention and their contents, the bonding property between the first welding rib material and the workpiece is improved, thereby improving the bonding property and sealing property of welding, and at the same time, the welding rib structure has the effects of anti-oxidation and antibacterial.
[0019] According to a specific embodiment of the present invention, preferably, in step S1, based on the total mass of the light absorber as 100%, carbon black 3%-5%, carbon nanotubes and / or graphene 5%-10%, azo (-N=N-) dyes 3%-5%, metal-porphyrin (-C=N-) complexes 3%-7% and the second solvent remainder. More preferably, the average length of the carbon nanotubes is 5-20 μm and the average diameter is 1-10 nm. More preferably, the graphene includes graphene powder, and its average particle size is less than 2 μm. The azo dye adopts a compound disclosed in the prior art, and the present invention does not impose special restrictions on it. More preferably, the metal in the metal-porphyrin complex includes one or more of iron, copper, zinc and cobalt. Specifically, the metal-porphyrin complex is, for example, but not limited to, one or more of tetrakis(4-N-ethylpyridyl)porphyrin iron (Fe(TEPyP)), copper tetrapyridoporphyrin (Cu(II)PTp), 5,10,15,20-tetrakis(4-bromophenyl)zinc porphyrin (ZnTBrPP) and meso-5,10,15,20-tetrakis(p-aminophenyl)cobalt porphyrin (Co-TAPP), etc. The second solvent includes an organic solvent, for example, but not limited to, N-methylpyrrolidone (NMP), etc.
[0020] The present invention adopts the above-mentioned composition as a light absorber, wherein the carbon black is used as the main light absorber; the carbon nanotubes and / or graphene can improve the heat conductivity while improving the light absorbance; the azo dyes can further improve the light absorbance; the metal-porphyrin complex can improve the strength of the weld rib while improving the light absorbance. Through the synergistic effect between the components of the light absorber of the present invention and their contents, the light absorbance of the overall weld rib structure is greatly enhanced, and the welding forming process is more reliable.
[0021] According to a specific embodiment of the present invention, preferably, in step S1, the mass ratio of the first thermoplastic material, the adhesive and the light absorber is (5-7): (2-4): (1-2).
[0022] According to a specific embodiment of the present invention, preferably, in step S1, the spraying device includes a sprayer, the first thermoplastic material, adhesive and light absorber are added to the heat pump of the sprayer, heated to above 250°C to form the first weld rib material, and then sprayed into the groove of the lower workpiece, the spraying temperature is above the melting temperature of the lower workpiece, and after cooling and solidification, a preliminary weld rib structure is formed. Among them, the heating method of the heat pump can be electric heating wire heating, etc. The cooling and solidification time can be determined based on the composition of the first weld rib material, which can generally be 3-10min. More preferably, the moving speed of the spray head of the sprayer is 10-40mm / s, the pump speed of the heat pump is 100-500r / min, and the order of spraying the first weld rib material is from the inner circle to the outer circle. By controlling the moving speed of the spray head, the pumping speed of the heat pump and the spraying sequence, the first weld rib material of the inner circle solidifies first, and the first weld rib material of the outer circle solidifies later, and the solidification of the first weld rib material can be controlled more accurately, thereby preventing the shrinkage and deformation of the lower workpiece caused by heat. More preferably, the heat pump temperature, spray head flow, spray head moving speed, spray head moving direction and forming height of the preliminary weld rib structure of the spray machine are controlled by PC programming. The spray machine adopts a device in the prior art, and the present invention does not impose any special restrictions on its structure.
[0023] According to a specific embodiment of the present invention, preferably, in step S2, based on the total mass of the second welding rib material as 100%, it includes: 60%-70% glass fiber, 0.5%-1.5% second coupling agent, 5%-10% heat-resistant additive, 0.1%-0.5% second antioxidant, 0.5%-1% heat stabilizer, 0.1%-0.3% lubricant and graphene remainder. More preferably, the glass fiber is E-glass fiber, which has the advantages of high modulus and high strength; further preferably, the average length of the E-glass fiber is less than 1mm and the average diameter of the monofilament is 3-10μm. More preferably, the second coupling agent includes a silane coupling agent, such as γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), etc. More preferably, the heat-resistant additive includes alumina nanoparticles, etc. More preferably, the second antioxidant includes a hindered phenol antioxidant, such as Irganox 1010, etc. More preferably, the thermal stabilizer includes a calcium zinc stabilizer, etc. More preferably, the lubricant includes zinc stearate, etc. More preferably, the graphene includes graphene powder, and the average particle size thereof is 2 μm or less.
[0024] The present invention adopts the above-mentioned composition as the second welding rib material, and through the action of the coupling agent, a strong chemical bridge is formed between the glass fiber and the workpiece, thereby enhancing the interface bonding force; through the joint action of the heat-resistant additive and the heat stabilizer, the stability of the welding rib material at high temperature is improved, and thermal damage is reduced; at the same time, the presence of the antioxidant protects the welding rib material from damage caused by thermal oxidative aging, and maintains long-term performance; moreover, the lubricant improves the processing performance of the welding rib material and reduces surface defects; graphene can improve the bonding strength, while improving the light absorption capacity and thermal conductivity. Through the synergistic effect between the components and their contents of the second welding rib material of the present invention, the bonding strength can be improved, and the thermal conductivity of the light absorption of the welding rib structure can be improved, thereby improving the welding strength.
[0025] According to a specific embodiment of the present invention, preferably, in step S2, the mass ratio of the second welding rib material to the first welding rib material is (10-20): (90-80).
[0026] The present invention sprays a second welding rib material containing glass fiber on the basis of the preliminary welding rib structure, so that it melts and wraps the preliminary welding rib structure, which can increase the mixing and interlacing between molecules, improve the energy absorption and reflection of the transmitted laser, promote the melting of the welding rib after welding, thereby improving the bonding strength, and improve the heat conduction effect of the welding rib structure absorbing light, thereby improving the welding strength and helping to form a high-quality weld. If the first welding rib material and the second welding rib material are mixed and sprayed at one time, it is easy to cause collapse and cannot form a high-quality weld.
[0027] According to a specific embodiment of the present invention, preferably, in step S2, the spraying device includes a sprayer, and the components of the second weld rib material are added to the heat pump of the sprayer, heated to above 250°C to form the second weld rib material, and then sprayed to the surface of the preliminary weld rib structure, and the second weld rib material wraps the preliminary weld rib structure, and the spraying temperature is above the melting temperature of the lower workpiece, and after cooling and solidification, the overall weld rib structure is formed. Among them, the heating method of the heat pump can be electric heating wire heating, etc. The cooling and solidification time can be determined based on the composition of the second weld rib material, which can generally be 3-10min. More preferably, the moving speed of the spray head of the sprayer is 10-40mm / s, the pump speed of the heat pump is 100-500r / min, and the order of spraying the second weld rib material is from the inner circle to the outer circle. Further preferably, the pump speed of the heat pump in step S2 is lower than the pump speed of the heat pump in step S1, so as to facilitate the pre-embedded filling of the preliminary weld rib structure. More preferably, the heat pump temperature, spray head flow, spray head moving speed and spray head moving direction of the spray machine are controlled by PC programming. It should be noted that in the process of spraying the second weld rib material, the second weld rib material should be made to evenly wrap the preliminary weld rib structure to avoid excessive or insufficient spraying in certain areas. The spray machine adopts a device in the prior art, and the present invention does not impose any special restrictions on its structure.
[0028] According to a specific embodiment of the present invention, in step S2, the height of the integral welding rib structure is 0.2-0.3 mm higher than the depth of the groove of the lower workpiece, and the width of the integral welding rib structure is 0.5-2 mm. The width of the integral welding rib structure should be smaller than the width of the groove of the lower workpiece. Based on the width of the groove, it is more appropriate to control the width of the integral welding rib structure to 0.5-2 mm, which is more conducive to obtaining a tight welding effect.
[0029] According to a specific embodiment of the present invention, preferably, in step S3, the method of superimposing and fixing the upper workpiece and the lower workpiece with the welding rib structure includes: superimposing and fixing the upper workpiece and the lower workpiece with the welding rib structure to a processing position, the contact surfaces of the upper workpiece and the lower workpiece with the welding rib structure forming a welding surface, placing a glass plate above the upper workpiece, and using a fixed torsion spring to apply a downward clamping force to fix it.
[0030] According to a specific embodiment of the present invention, preferably, in step S3, the laser welding device includes a semiconductor continuous laser or a fiber continuous laser, the laser wavelength used is 900-1000nm, the welding power is controlled to be 10-500w, and the welding rate is 2-20mm / s. By controlling the laser welding device used, as well as the laser wavelength and the parameters of the welding process within the above range, the heating temperature of the heat source generated by the laser beam is lower than the melting temperature of the upper workpiece, and higher than the melting temperature of the overall weld rib structure, so that the laser beam passes through the upper workpiece, concentrates the energy on the overall weld rib structure of the lower workpiece, melts it, and combines the upper workpiece and the lower workpiece into one under pressure. More preferably, during the welding process, the welded upper workpiece and the lower workpiece with the weld rib structure move in the X and Y directions, and the welding head of the laser welding device moves in the Z direction.
[0031] According to a specific embodiment of the present invention, preferably, in step S3, the downward clamping force is applied by using a fixed torsion spring, and the torque of the fixed torsion spring is 10-15 Nm.
[0032] A second aspect of the present invention provides a welded structural member, which is prepared by the above-mentioned welding method using glass fiber reinforcement.
[0033] A third aspect of the present invention provides the use of the above-mentioned welded structural member in a plate-frame structural member of a flow battery and / or a structural member in an automobile.
[0034] The present invention has at least the following beneficial effects:
[0035] The present invention uses a spraying device to realize the automation of the welding rib spraying process, facilitates the control of the size of the welding rib structure, eliminates the integrated machining between the welding rib and the workpiece, reduces the workload of auxiliary welding black cleaning, and effectively compensates for the unevenness of the workpiece surface after laser welding, improves the processing accuracy, and improves the bonding performance and sealing performance of welding. In addition, the present invention first sprays the first welding rib material to form a raised preliminary welding rib structure, which plays a positioning role on the one hand, and serves as a light-absorbing bottom layer on the other hand to assist welding. Through the synergistic effect between the first thermoplastic material, adhesive and light absorbent of the present invention, the bonding property of the first welding rib material and the workpiece is improved, thereby improving the bonding performance and sealing performance of welding, while making the welding rib structure have anti-oxidation, antibacterial and other effects, and greatly enhancing the light absorption of the overall welding rib structure. On the basis of the preliminary weld rib structure, the present invention sprays a second weld rib material containing glass fiber to melt and evenly wrap the preliminary weld rib structure, which can increase the mixing and interlacing between molecules, improve the energy absorption and reflection of the transmitted laser, promote the melting of the weld rib after welding, thereby improving the bonding strength, and improve the heat conduction effect of the weld rib structure absorbing light, thereby improving the welding strength, which is helpful to form a high-quality weld. Subsequently, the present invention places the upper workpiece to be welded above the lower workpiece with the weld rib structure, and melts the weld rib structure flat through the heat generated by the laser transmission welding technology, thereby bonding the upper and lower workpieces. The present invention simplifies the process flow of laser transmission welding, saves production costs and time, improves processing accuracy, and is easy to realize automation. Moreover, the present invention can also avoid the limitation of the weld rib on the workpiece material, does not need to rely on the material of the lower workpiece to be light-absorbing, and only ensures the light-absorbing property of the weld rib material, so that the upper and lower workpieces of different materials can be stacked and welded more easily, avoiding the duplication of weld ribs, and further broadening the application of laser welding technology in the fields of plate frame of liquid flow battery, automobile manufacturing, etc. The present invention overcomes the drawbacks of the existing laser transmission welding process, solves the problem of the cumbersome machining process of the integrated welding rib and the workpiece, solves the problem of the workpiece needing to add an additional light absorbent to meet the light absorption of the welding rib, and overcomes the problem of unevenness on the workpiece surface after welding. In particular, the present invention is suitable for application in the plate-frame structural parts of liquid flow batteries, has good bonding and sealing effects, makes up for the problem of uneven bonding surfaces of the two workpieces caused by plate-frame molding, and avoids the process of milling grooves and welding convex ribs in the plate-frame machining, greatly shortening the processing time. The present invention can effectively avoid the leakage of electrolyte in the liquid flow battery stack due to welding, improve the reliability of the efficient sealing assembly of the liquid flow battery stack, extend the service life of the liquid flow battery stack, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the overall welding rib structure in an embodiment of the present invention.
[0037] Figure 2 Schematic diagram of a welded structural member in an embodiment of the present invention.
[0038] Figure 3 Schematic diagram of the sample structure for the pull-out test.
[0039] Figure 4 This is the original morphology of the weld rib structure in Example 1.
[0040] Figure 5 This is a morphology diagram of the weld rib structure after being damaged by drawing in Example 1.
[0041] Figure 6 The pull-out force and tensile fracture bonding stress of the pull-out test in Example 1 vary with the power density of laser welding.
[0042] Description of Figure Numbers:
[0043] 1-laser beam; 2-upper workpiece; 3-lower workpiece; 4-integral weld rib structure; 5-groove; 6-weld rib structure in the welded structural part. DETAILED DESCRIPTION
[0044] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the present invention is now described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.
[0045] It should be noted that, unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.
[0046] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0047] It should be understood that the terms "comprises," "comprising" and / or "containing" when used herein specify the presence of stated features, integers, steps, components or combinations thereof, but do not preclude the presence or addition of one or more other features, integers, steps, components or combinations thereof.
[0048] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0049] Example 1
[0050] This embodiment provides a welding method using glass fiber reinforcement, such as Figure 1 and Figure 2 As shown, it includes the following steps:
[0051] First, the spraying device used in this embodiment is a spraying machine, and the heat pump temperature, spray head flow, spray head moving speed, spray head moving direction and the forming height of the preliminary weld rib structure of the spraying machine are controlled by PC programming. The laser welding device used in this embodiment is a fiber continuous laser with a wavelength of 980nm.
[0052] Then, a substrate with a groove 5 processed on the surface is prepared as the lower workpiece 3, and fixed on the processing position. The thickness of the lower workpiece 3 is more than 3 mm. The groove 5 of the lower workpiece 3 has a depth of 0.35 mm and a width of 2.5 mm, and the groove 5 of the lower workpiece 3 has a plurality of raised stripes with a width of 0.1 mm and a height of 0.2 mm.
[0053] Afterwards, the first thermoplastic material, adhesive and light absorber are added to the heat pump of the sprayer, heated to above 250°C to melt and mix the first thermoplastic material, adhesive and light absorber to form the first weld rib material, and then the spray head of the sprayer is aligned with the groove 5, and then the first weld rib material is sprayed into the groove 5 of the lower workpiece 3, the spraying temperature is above the melting temperature of the lower workpiece 3, the moving speed of the spray head of the sprayer is 40mm / s, the pump speed of the heat pump is 200-500r / min, and the order of spraying the first weld rib material is from the inner circle to the outer circle. After the spraying is completed, wait for 3 minutes to cool and solidify naturally to form a preliminary weld rib structure, which is a convex structure, and the height of the preliminary weld rib structure is 0.2mm. The heating method of the heat pump can be heating with an electric heating wire, etc. At the same time, preparations can be made for spraying the second weld rib material.
[0054] The first thermoplastic material is polypropylene (PP-Y20), which is the same as the main material of the lower workpiece 3 .
[0055] Taking the total mass of the adhesive as 100%, the adhesive comprises: modified polypropylene (PP-CF20) 70%, carbon fiber (average length of 0.1 mm, diameter of 5-10 μm) 15%, graphene nanosheets (average thickness of 7 nm, average diameter of the sheet layer of 13 μm) 1%, γ-aminopropyltrimethoxysilane 0.5%, hindered phenol antioxidant Irganox 1010 0.3%, silver ion antibacterial agent SILVADUR 930 0.2%, hollow glass microspheres (average particle size of 180 μm, bulk density of 0.2 g / cm 3 ) 5%, nano-montmorillonite (average particle size of 14nm) 5% and epoxy acrylate oligomer (Laromer-EA 8765R) the rest.
[0056] Taking the total mass of the light absorber as 100%, it includes: 3% carbon black, 2.5% carbon nanotubes (average length of 10 μm, average diameter of 1.5 nm), 2.5% graphene powder (average particle size of less than 2 μm), 3% Congo red, 5% 5,10,15,20-tetrakis(4-bromophenyl)zinc porphyrin, and 84% N-methylpyrrolidone.
[0057] The mass ratio of the first thermoplastic material, the adhesive and the light absorber is 6:2:2.
[0058] The components of the second weld rib material are added to the heat pump of the sprayer, heated to above 250°C to form the second weld rib material, and then sprayed to the surface of the preliminary weld rib structure, and the second weld rib material is made to evenly wrap the preliminary weld rib structure. The spraying temperature is above the melting temperature of the lower workpiece 3, the moving speed of the spray head of the sprayer is 40mm / s, the pump speed of the heat pump is 100-300r / min, and the order of spraying the second weld rib material is from the inner circle to the outer circle. After the spraying is completed, wait for 10 minutes for natural cooling and solidification to form an overall weld rib structure 4. The height of the overall weld rib structure 4 is 0.55mm (i.e., 0.2mm higher than the depth of the groove 5) and the width is 1.5mm. The lower workpiece 3 with a weld rib structure is obtained, and its morphology is as follows Figure 4 shown.
[0059] Among them, taking the total mass of the second welding rib material as 100%, it includes: 70% of E-glass fiber (average length of less than 1 mm, single filament diameter of 3-10 μm), 1% of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 7% of aluminum oxide nanoparticles (particle size of 10-40 nm), 0.3% of hindered phenol antioxidant Irganox 1010, 1% of calcium zinc stabilizer SAK-CZL56-NP, 0.2% of zinc stearate and the remainder of graphene powder (average particle size of less than 2 μm).
[0060] The mass ratio of the second welding rib material to the first welding rib material is 1:8.
[0061] Then, the upper workpiece 2 is superimposed on the lower workpiece 3 with the welding rib structure, and the contact surface of the upper workpiece 2 and the lower workpiece 3 with the welding rib structure forms a welding surface. A glass plate is placed on the upper workpiece 2, and a fixed torsion spring is used to apply a downward clamping force to fix it. Then the fiber continuous laser is turned on to emit a laser beam 1, which passes through the upper workpiece 2 and acts on the overall welding rib structure 4. The welding power is controlled to be 100w and the welding rate is 20mm / s. Under the action of the laser, the overall welding rib structure 4 melts to stimulate its adhesion. At the same time, a fixed torsion spring is used to apply a downward clamping force. The torque of the fixed torsion spring is 10Nm, so that the upper workpiece 2 and the lower workpiece 3 are welded together. During the welding process, the welded upper workpiece 2 and the lower workpiece 3 with the welding rib structure move in the X and Y directions, and the welding head of the fiber continuous laser moves in the Z direction. After the welding is completed, the fiber continuous laser is turned off and the pressure is maintained for 15s to improve the adhesion and sealing.
[0062] The main material of the upper workpiece 2 is polypropylene (PP-Y20), and its light transmittance is above 30%.
[0063] Finally, after natural cooling, the weld is solidified to obtain a welded structural part. Figure 2 shown.
[0064] The welded structural member of this embodiment was subjected to a pull-out test and an air-tightness test.
[0065] The steps of the pull-out test include: (1) preparing an upper workpiece and a lower workpiece, both of which have a length and width of 100 mm × 30 mm and a thickness of 3 mm; (2) orthogonally welding the upper workpiece and the lower workpiece to prepare a sample, such as Figure 3 As shown in FIG. 1 , the size of the central overlapping area of the upper workpiece and the lower workpiece is 30 mm × 30 mm, and the depth of the welding area (i.e., the groove) is 0.35 mm, the length is 10 mm, and the width is 2.5 mm; (3) The upper workpiece and the lower workpiece are connected to a universal testing machine and a tensile test is performed. The tensile directions of the upper workpiece and the lower workpiece are as follows: Figure 3 (4) Adjust the speed of the universal testing machine in the tensile direction to 5 mm / min until the peak value is recorded as the pull-out force after cracking. The same group of samples shall be tested for no less than 3 times and the average value shall be taken. (5) The tensile fracture bond stress is calculated using the peak pull-out force and the welding area: Tensile fracture bond stress (Mpa) = pull-out force (N) ÷ welding area (m 2 ).
[0066] In addition, based on this embodiment, the welding power and welding rate of laser welding are adjusted, the adjustment range of welding power is 10-500w, and the adjustment range of welding rate is 2-20mm / s, so that the welding power density is as follows: Figure 6The values shown on the horizontal axis are obtained to prepare different welded rib structures, and the pull-out tests are performed respectively. It should be noted that welding power density (J / mm) = welding power (w) ÷ welding speed (mm / s).
[0067] The results of the pull-out test are: Figure 4 , Figure 5 and Figure 6 As shown, the original morphology of the weld rib structure of this embodiment is good. After the pull-out test, the weld rib structure is broken, and its tensile fracture bonding stress is ≥3Mpa.
[0068] The steps of the airtightness test include: (1) preparing a box-shaped lower workpiece with a cavity, a threaded through hole is opened on the side of the lower workpiece, and a weld rib structure is circumferentially arranged around the periphery of the cavity (a groove is arranged on the periphery of the cavity with a depth of 0.35 mm and a width of 2.5 mm), and the upper workpiece is welded along the weld rib structure; (2) after welding is completed, tighten the airtight joint in the threaded through hole of the lower workpiece, and inflate until the pressure inside the welded structure reaches 500 kPa; (3) maintain the pressure for 20 minutes, and observe the leakage through the pressure gauge set at the threaded through hole. The leakage is qualified if it is less than 5 kPa.
[0069] The result of the air tightness test is: meeting the design requirements, and the leakage is less than 3kpa.
[0070] From the results of the above-mentioned pull-out test and airtightness test, it can be seen that the welded structural member of this embodiment has high welding strength and airtightness.
[0071] Example 2
[0072] This embodiment is basically the same as Embodiment 1, except that:
[0073] Taking the total mass of the adhesive as 100%, it includes: 50% of modified polypropylene (PP-CF20), 20% of carbon fibers (average length of 0.12 mm and diameter of 5-10 μm), 5% of graphene nanosheets (average thickness of 8 nm and sheet diameter of 25 μm), 0.8% of γ-aminopropyltrimethoxysilane, 0.3% of hindered phenol antioxidant Irganox 1010, 0.2% of silver ion antibacterial agent SILVADUR 930, 10% of hollow glass microspheres (average particle size of 200 μm and bulk density of 0.25 g / cm3), 5% of nano-montmorillonite (average particle size of 16 nm) and the remainder of epoxy acrylate oligomer (Laromer-EA 8765R).
[0074] Taking the total mass of the light absorber as 100%, it includes: 5% carbon black, 5% carbon nanotubes (average length of 15 μm, average diameter of 2 nm), 5% graphene powder (average particle size of less than 2 μm), 5% Congo red, 3% tetrapyridoporphyrin copper and 77% N-methylpyrrolidone.
[0075] The mass ratio of the first thermoplastic material, the adhesive and the light absorber is 7:2:1.
[0076] The rest are the same as in Example 1.
[0077] The welded structure of this embodiment was subjected to a pull-out test and an air tightness test. The test steps were the same as those of Example 1. The result of the pull-out test was that the tensile fracture bonding stress of the welded rib structure of this embodiment was ≥3.2Mpa. The result of the air tightness test was that the design requirements were met and the leakage was less than 4.2kpa.
[0078] Example 3
[0079] This embodiment is basically the same as Embodiment 1, except that:
[0080] Taking the total mass of the second welding rib material as 100%, it includes: 60% of E-glass fiber (average length of less than 1 mm, single filament diameter of 3-10 μm), 1.5% of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 10% of aluminum oxide nanoparticles (particle size of 10-40 nm), 0.3% of hindered phenol antioxidant Irganox 1010, 0.5% of calcium zinc stabilizer SAK-CZL56-NP, 0.2% of zinc stearate and the remainder of graphene powder (average particle size of less than 2 μm).
[0081] The mass ratio of the second welding rib material to the first welding rib material is 1:9.
[0082] The rest are the same as in Example 1.
[0083] The welded structure of this embodiment was subjected to a pull-out test and an air tightness test. The test steps were the same as those of Example 1. The result of the pull-out test was that the tensile fracture bonding stress of the welded rib structure of this embodiment was ≥3.5Mpa. The result of the air tightness test was that the design requirements were met and the leakage was less than 2kpa.
[0084] Comparative Example 1
[0085] This comparative example is basically the same as Example 1, except that: the second welding rib material is not used, the amount of the first welding rib material is increased, and the height of the preliminary welding rib structure is 0.55 mm and the width is 1.5 mm. That is, after the preliminary welding rib structure is formed, laser welding is performed. The rest is the same as Example 1.
[0086] The welded structural parts of this comparative example were subjected to a pull-out test and an air tightness test. The test steps were the same as those of Example 1. The result of the pull-out test was that the tensile fracture bonding stress of the welded rib structure of this comparative example was 2.5 MPa. The result of the air tightness test was that the design requirements were met, but the leakage increased to 5 kPa.
[0087] Comparative Example 2
[0088] This comparative example is basically the same as Example 1, except that the components of the first thermoplastic material, the adhesive, the light absorber and the second welding rib material are added together into the heat pump of the sprayer, and only one spraying is performed to obtain the welding rib structure, and then laser welding is performed. The heating temperature of the heat pump, the moving speed of the spray head, the pumping speed of the heat pump, etc. are the same as those in Example 1. The rest are also the same as those in Example 1.
[0089] The welded structural parts of this comparative example were subjected to a pull-out test and an air tightness test. The test steps were the same as those of Example 1. The result of the pull-out test was that the tensile fracture bonding stress of the welded rib structure of this comparative example was 2.2 Mpa. The result of the air tightness test was that the leakage reached 6 kpa, which failed to meet the design requirements.
[0090] Comparative Example 3
[0091] This comparative example is basically the same as Example 1, except that: no adhesive is used in the first welding rib material, the mass ratio of the first thermoplastic material to the light absorber and the mass ratio of the second welding rib material to the first welding rib material are the same as those in Example 1, and the height and width of the overall welding rib structure are also the same as those in Example 1. The rest is the same as in Example 1.
[0092] The welded structural parts of this comparative example were subjected to a pull-out test and an air tightness test. The test steps were the same as those of Example 1. The result of the pull-out test was that the tensile fracture bonding stress of the welded rib structure of this comparative example was 2.0 MPa. The result of the air tightness test was that the leakage was 10 kPa, which failed to meet the design requirements.
[0093] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A welding method using glass fiber reinforcement, comprising the following steps: Step S1: using a spraying device to spray a first welding rib material into the groove of the lower workpiece, and after cooling and solidification, forming a preliminary welding rib structure; the first welding rib material includes a first thermoplastic material, an adhesive and a light absorbent; Step S2: using a spraying device to spray a second welding rib material onto the surface of the preliminary welding rib structure, and wrapping the preliminary welding rib structure with the second welding rib material, and after cooling and solidification, forming an integral welding rib structure, and obtaining a lower workpiece having a welding rib structure; the second welding rib material includes glass fiber; Step S3: superimpose and fix the upper workpiece and the lower workpiece with the weld rib structure, use a laser welding device to emit a laser beam, pass through the upper workpiece, act on the overall weld rib structure, melt the overall weld rib structure, and at the same time apply a downward clamping force to weld the upper workpiece and the lower workpiece into one, so as to obtain a welded structural part.
2. The welding method using glass fiber reinforcement according to claim 1, wherein: The thickness of the lower workpiece is more than 3 mm; the depth of the groove of the lower workpiece is 0.3-0.5 mm, the width is 1-5 mm, and the groove of the lower workpiece has a plurality of raised stripes with a width of 0.1±0.03 mm and a height of 0.2±0.05 mm; Preferably, the light transmittance of the upper workpiece is above 30%.
3. The welding method using glass fiber reinforcement according to claim 1, wherein: In step S1, the melting point of the first thermoplastic material is 170-185°C; Preferably, the first thermoplastic material is the same as the bulk material of the lower workpiece; More preferably, the first thermoplastic material comprises polypropylene, acrylonitrile-styrene-butadiene copolymer or polyphenylene ether.
4. The welding method using glass fiber reinforcement according to claim 1, wherein: In step S1, based on the total mass of the adhesive being 100%, the adhesive comprises: 50%-70% of a second thermoplastic material, 10%-20% of carbon fiber, 1%-5% of graphene, 0.2%-0.8% of a first coupling agent, 0.1%-0.4% of a first antioxidant, 0.05%-0.2% of an antibacterial agent, 5%-10% of hollow glass microspheres, 3%-7% of nanoclay, and the remainder of a first solvent; Preferably, the main body material of the second thermoplastic material is the same as the first thermoplastic material; the first coupling agent includes a silane coupling agent; the first antioxidant includes a hindered phenol antioxidant; the antibacterial agent includes a silver ion antibacterial agent; and the first solvent includes an epoxy acrylate polymer.
5. The welding method using glass fiber reinforcement according to claim 1, wherein: In step S1, based on the total mass of the light absorber being 100%, the light absorber comprises: 3%-5% carbon black, 5%-10% carbon nanotubes and / or graphene, 3%-5% azo dyes, 3%-7% metal-porphyrin complexes, and the remainder of the second solvent; Preferably, the metal in the metal-porphyrin complex includes one or more of iron, copper, zinc and cobalt; more preferably, the metal-porphyrin complex includes one or more of tetrakis(4-N-ethylpyridyl)porphyrin iron, tetrakispyridoporphyrin copper, 5,10,15,20-tetrakis(4-bromophenyl)zincporphyrin and meso-5,10,15,20-tetrakis(p-aminophenyl)cobaltporphyrin; Preferably, the second solvent comprises an organic solvent.
6. The welding method using glass fiber reinforcement according to claim 1, wherein: In step S1, the mass ratio of the first thermoplastic material, the adhesive and the light absorber is (5-7):(2-4):(1-2).
7. The welding method using glass fiber reinforcement according to claim 1, wherein: In step S1, the spraying device includes a sprayer, the first thermoplastic material, the adhesive and the light absorber are added to the heat pump of the sprayer, heated to above 250° C. to form the first weld rib material, and then sprayed into the groove of the lower workpiece at a spraying temperature above the melting temperature of the lower workpiece, and after cooling and solidification, a preliminary weld rib structure is formed; Preferably, in step S1, the moving speed of the spray head of the spray machine is 10-40 mm / s, the pump speed of the heat pump is 100-500 r / min, and the order of spraying the first welding rib material is from the inner circle to the outer circle.
8. The welding method using glass fiber reinforcement according to claim 1, wherein: In step S2, taking the total mass of the second welding rib material as 100%, it includes: 60%-70% of glass fiber, 0.5%-1.5% of a second coupling agent, 5%-10% of a heat-resistant additive, 0.1%-0.5% of a second antioxidant, 0.5%-1% of a heat stabilizer, 0.1%-0.3% of a lubricant, and a remainder of graphene; Preferably, the glass fiber is E-glass fiber, and the length of the E-glass fiber is less than 1 mm; the second coupling agent includes a silane coupling agent; the heat-resistant additive includes aluminum oxide nanoparticles; the second antioxidant includes a hindered phenol antioxidant; the heat stabilizer includes a calcium zinc stabilizer; and the lubricant includes zinc stearate; Preferably, the mass ratio of the second welding rib material to the first welding rib material is (10-20):(90-80).
9. The welding method using glass fiber reinforcement according to claim 1, wherein: In step S2, the spraying device includes a sprayer, and the components of the second weld rib material are added to the heat pump of the sprayer, heated to above 250° C. to form the second weld rib material, and then sprayed onto the surface of the preliminary weld rib structure, and the second weld rib material wraps the preliminary weld rib structure, the spraying temperature is above the melting temperature of the lower workpiece, and after cooling and solidification, an integral weld rib structure is formed; Preferably, in step S2, the moving speed of the spray head of the spray machine is 10-40 mm / s, the pump speed of the heat pump is 100-500 r / min, and the order of spraying the second welding rib material is from the inner circle to the outer circle; Preferably, in step S2, the height of the integral weld rib structure is 0.2-0.3 mm higher than the depth of the groove of the lower workpiece, and the width of the integral weld rib structure is 0.5-2 mm.
10. The welding method using glass fiber reinforcement according to claim 1, wherein: In step S3, the method of superimposing and fixing the upper workpiece and the lower workpiece with the welding rib structure includes: superimposing and fixing the upper workpiece and the lower workpiece with the welding rib structure to a processing position, the contact surfaces of the upper workpiece and the lower workpiece with the welding rib structure forming a welding surface, placing a glass plate above the upper workpiece, and using a fixed torsion spring to apply a downward clamping force to fix it; Preferably, in step S3, the laser welding device comprises a semiconductor continuous laser or a fiber continuous laser, the laser wavelength used is 900-1000nm, the welding power is controlled to be 10-500w, and the welding rate is 2-20mm / s; Preferably, in step S3, the downward clamping force is applied by using a fixed torsion spring, and the torque of the fixed torsion spring is 10-15 Nm.
11. A welded structural part, which is prepared by the welding method using glass fiber reinforcement according to any one of claims 1 to 10.
12. Use of the welded structural member according to claim 11 in plate-frame structural members of a flow battery and / or structural members in an automobile.
Citation Information
Cited By
Preparation method of plate frame material for direct stack welding of flow batteries, plate frame and plate frame welding process
CN120518954A
A method of preparing a plate and frame material for direct stack welding of a flow battery, a plate and frame, and a plate and frame welding process
CN120518954B